Enhancing Students' Learning Motivation with Interactive Educational Game Media Based on Articulate Storyline 3 in IPAS Learning for Grade V Elementary School - Aris Purwanto; Tri Murwaningsih; Mintasih Indriayu (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Low learning motivation among elementary school students in rural areas is an urgent issue that requires innovative solutions. This study aimed to increase students’ learning motivation through interactive educational games developed with Articulate Storyline 3 in science and social learning (IPAS). The research employed Classroom Action Research (CAR) using the Kemmis & McTaggart model, conducted in two cycles involving 17 fifth-grade students at Banyurip State Elementary School, Boyolali Regency. Data were collected using an ARCS-based motivation questionnaire (Attention, Relevance, Confidence, Satisfaction), observation sheets, interviews, and documentation. The results showed a significant improvement in all ARCS aspects, with active student participation increasing from 50% to over 80%. These findings confirm the effectiveness of Storyline 3-based interactive games in fostering motivation. The novelty of this study lies in applying the ARCS model through Articulate Storyline 3 in rural elementary schools, which has rarely been examined in previous research.